Experimental Study on the Fracture Evolution Processof Rock-like Specimens Containing a Closed RoughJoint Based on 3D-Printing Technology - Jiawei Liu; Haijian Su; Hongwen Jing; Chengguo Hu; Qian Yin (Advances in Civil Engineering)
In order to overcome the disadvantage of traditional joint fabrication method—inability to reproduce the rough surfaces of practical rock joints—3D-printing technology was applied to restructure five kinds of rough joint according to the failure surface formed by the triaxial prepeak unloading test in this study. And uniaxial compression test was carried out on the rock-like specimens containing closed 3D-printing rough joint to study the effects of joint inclination and joint length on the mechanical properties (peak strength, peak strain, elastic modulus, and secant modulus), cracking process, and failure modes. Besides, digital image correlation (DIC) method and acoustic emission (AE) system are used to investigate the whole evolution process of strain fields and crack propagation during loading. It is found that the mechanical parameters decrease first and then go up as the joint inclination increases, while presenting a continuous downward trend with the increase of joint length. Inclination of 45° and the larger joint length bring more extensive reduction to mechanical properties of specimens. Specimens exhibit typical brittle failure characteristics. The failure mode of specimens affected by different joint inclination is tension-shear failure. And the joint scale rises; the failure mode of specimens changes from tensile failure to shear failure. Larger joint scale results in the longer prepeak fluctuation phase on axial stress-strain curves and more dispersed distribution of high-value AE counts.